Consumer preference of beef rib steaks from implanted steers, implanted and non-implanted bulls - C.D. Pelton; Dell M. Allen; L.R. Corah; George A. Milliken (Kansas Agricultural Experiment Station Research Reports, 1984)
Our research showed that implanting bulls from birth to slaughter made steaks from bulls as acceptable as steers to consumer panels. Implanting bulls from weaning to slaughter resulted in the least desirable consumer panel ratings for all palatability traits measured.
Keywords: Cattlemen' s Day; 1984; Kansas Agricultural Experiment Station contribution; no. 84-300-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 448; Beef; Rib steak; Implants; Steers; Bulls